Considerações sobre a demonstração original do teorema da completude de Kurt Gödel - Sanctos, Cassia Sampaio (2015)
The thesis constitutes a critical review of Gödel´s doctoral dissertation which presents a proof for the completeness of first order logic. The introduction addresses the concepts of formalism, axiomatic method and completeness, thus the proof can be contextualized. The language for the restricted functional calculus is defined, with the corresponding syntax and semantics, and the original Gödel´s demonstration is updated. The appendix contains a translation of the referred dissertation, which is unprecedented in Portuguese